A global perspective on assisted reproductive technology fertility treatment: an 8-country fertility specialist survey. Issue 1 (December 2015) - Audibert, Céline; Glass, Daniel
Abstract Background Procedures that may optimize success in achieving live births from assisted reproductive technology (ART) continue to be examined. Not yet considered are the perspectives of fertility specialists regarding important developments in the fertility treatment field, current unmet needs, and anticipated future advances. In the current study, an 8-country survey of fertility specialists was conducted to provide a comprehensive, global depiction of fertility treatments across different regions. Methods Fertility specialists from France, Germany, Italy, Spain, the United Kingdom (UK), the United States (US), China, and Japan were invited to participate in an online survey. Participants were eligible if they personally managed ≥25 patients/month who were experiencing difficulty conceiving, and if they had performed ART fertility treatment with ≥1 patient in the previous month. Quantitative questions addressed the number of patients seen, main infertility causes, number of cycles performed, ART procedure type, and ART outcomes. Qualitative questions covered diagnostic trends, unmet needs, important advances, and expected future developments. Results The number of fertility specialists who completed the survey included 29 in France, 33 in Germany, 23 in Italy, 38 in Spain, 34 in the UK, 91 in the US, 50 in China, and 65 in Japan. Patient volume increased over the prior 2 years according to 67 % (242/363) of the fertility specialists. As expected, ART outcomes all declined with age in all countries. ART outcomes varied by country, with the highest implantation, pregnancy, and live birth rates reported by fertility specialists in the US and China and the lowest rates reported in France and Italy. The most frequently reported unmet needs in fertility treatment were financial coverage, improved implantation rate, and egg donation. Most frequently named future advancements expected to change the fertility treatment field included improved embryo selection through imaging and/or metabolomics, improved embryo implantation rate, and use of preimplantation genetic diagnosis. Conclusions This study, which follows a rigorous survey methodology, elucidates the current state of fertility specialists' practices and perspectives on the global fertility treatment field, which highlights differences and similarities among countries. This research may inform further studies and procedural developments that might better improve and standardize ART.